"Truth behind bars" : reflections on the fate of the Russian Revolution - Kellogg, Paul, 1955- (AU Press, 2021)
"Following the 1917 Russian Revolution, the arctic settlement of Vorkuta was the site of a notorious Gulag that held former Trotsky followers and members of the Left Opposition. This coal-mining town was a witness, first to the last stand of the Russian oppositional socialists, and second to a strike wave that sounded the death knell for the Stalinist forced labour system, overturned in 1991. Kellogg uses the backdrop of Vorkuta to argue for a return to the work of Iulii Martov--a contemporary of Lenin--and his analysis of a temporary class of peasants-in-uniform produced by the Great War. Coming from the trenches, Kellogg demonstrates that this class, led by Lenin and the Bolshevik Party, often relied on undemocratic and substitutionist policies to advance the revolutionary project. Ultimately, their actions thwarted the efforts made to establish an alternative to capitalism in the USSR and explain why democratic governance failed to become integrated into the Bolsheviks' theoretical perspectives and political practice."--